LARVICIDAL EFFECT OF THE SEED OILS OF TWO INDIGENOUS PLANTS FROM THE ALGERIAN SAHARA ON THE DESERT LOCUST (Acta Entomologica Serbica, 2021)
The lethal and sublethal effects of the seed oils of two indigenous plants of the Algerian Sahara, Peganum harmala L. (Zygophyllaceae) and Datura stramonium L. (Solanaceae), were investigated. Administration of 60 μl of oil by forced oral injection using a micropipette to the L5 larvae of Schistocerca gregaria Forsk. (Orthoptera: Acrididae) revealed the deterrent effect of these oils on treated larvae. The treatment resulted in various toxicological symptoms, such as intense defecation, diarrhea, weight loss, reduction in motor activity, delay and difficulty in molting and, in the most extreme cases, the death of treated individuals. During the treatment of L5 larvae of S. gregaria with P. harmala seed oil, various toxicological symptoms appeared: 81.81% of individuals presented with diarrhea; 68.18% of individuals lost weight; 72.72% exhibited reduced motor activity, and 100% of surviving individuals experienced a delay in their molt. On the other hand, in L5 larvae treated with D. stramonium seed oil, 77.27% of individuals had diarrhea, 100% showed weight loss and 100% of individuals reduced their motor activity. D. stramonium seed oil has been shown to be more toxic than P. harmala seed oil. The oral administration of 60 μl of D. stramonium seed oil caused the blocking of the phenomenon of exuviation in 100% of the treated L5 larvae, resulting in death after 16 days. While P. harmala seed oils caused 50% mortality after 12 days, the 50% surviving individuals were able to complete their imaginal molt with difficulties, which resulted in malformations. The estimated lethal time 50 (LT50) in larvae (L5) treated with D. stramonium seed oil was 3.67 days. It was more toxic than the LT50 obtained in larvae (L5) treated with the oil of P. harmala seeds, which was 12 days.The food intake in L5 larvae of S. gregaria treated with D. stramonium seed oil was 0.28 ± 0.18 g/day, it was lower than the average daily consumption recorded in the L5 larvae treated with P. harmala seed oil, which was 0.67 ± 0.36 g/day, D. stramonium seed oil appears to be more toxic, and profoundly affects food intake. The values of the apparent digestive utilization coefficient (DUC a) reported for L5 larvae treated with seed oil of P. harmala and D. stramonium were 39.32 ± 13.07% and 34.23 ± 29,07%, respectively. These values were significantly lower compared to the control group value, which was 70.63 ± 19.56%. Likewise, the digestive conversion coefficients (CCD) recorded in the L5 of S. gregaria treated with the seed oils of P. harmala and D. stramonium were -75.07 ± 54.45% and -3.08 ± 1.18, respectively. However, in the control group of L5 larvae, the noted CCD was 1.004 ± 0.073. Values of the consumption index (CI) reported for L5 larvae treated with the seed oils of P. harmala and D. stramonium were low, 6.74 ± 4.45 and 3.82 ± 2.45, respectively, while for the L5 larvae of the control group, it was 15.74 ± 3.51.